Karakteristik Teh Oolong Organik Celup (Camellia sinensis) dengan Perbedaan Waktu Oksidasi Enzimatis - Sri Dewi, Komang Ayu; Ari Yusasrini, Ni Luh; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p04, 2023)
This research aimed to identify the effect of differences in enzymatic oxidation time on the characteristics of organic oolong tea bags and to obtain the right enzymatic oxidation time to produce organic oolong tea bags with the best characteristics. This study used a completely randomized design (CRD) with the enzymatic oxidation time as the treatment which consist of 6 levels oxidation time for 15, 30, 45, 60, 75 and 90 minutes. The treatment was repeated 3 times to produce 18 experimental units. The data obtained by analysis of variance and if the treatment had a significant effect (P<0.05) on the observed variables, it was continued with Duncan’s Multiple Range Test. The results showed that the treatment of enzymatic oxidation time had a very significant effect on water content, extract content in water, total phenolic content, total flavonoid content, tannin content, antioxidant activity, color, taste, flavor, overall acceptance, color score and bitter taste score of organic oolong tea bags. The best treatment was 30 minutes enzymatic oxidation time that produced organic oolong tea bags with the characteristics 2.59% of water content, extract content in water 87.31%, total phenolic content 405.07 mgGAE/g, total flavonoid content 7.83 mgQE/g, tannins content 119.75 mgTAE/g, antioxidant activity 54.45%, the color was liked with brownish yellow color, aroma was liked, taste was liked with slightly bitter, flavor was liked, and overall acceptance was liked.